Is packaging affecting consumers' preferences for meat products? A study of modified atmosphere packaging and vacuum packaging in Iberian dry‐cured ham. Issue 4 (27th April 2020) - Ortiz, Alberto; Tejerina, David; Díaz‐Caro, Carlos; Elghannam, Ahmed; García‐Torres, Susana; Mesías, Francisco J.; Trujillo, José; Crespo‐Cebada, Eva
Abstract: Iberian dry‐cured ham is one of the most prominent Spanish traditional meat products with very special nutritional and sensory properties, which make it widely appreciated both in Spain and in foreign markets. The packaging formats used for sliced Iberian ham are vacuum and modified atmosphere packaging, which are more in line with the current trends and consumer habits and have contributed to its popularization. The aim of this article is to study the preferences of Spanish consumers for these two types of packaging of Iberian dry‐cured ham using a dual approach with sensory analysis and choice experiment. Data were collected by means of a survey conducted with 253 Spanish consumers. The choice experiment has shown that the participants proved to have a higher preference for the vacuum packaging. However, sensory test revealed that hams packaged in modified atmosphere received higher scores in terms of odor when making a global comparison. Practical Applications: New purchasing habits require the adaptation of traditional products to new formats more in consonance with current consumer lifestyles. Iberian ham is one of these traditional products that until now selling in a whole‐piece format, which does not seem affordable for many consumers. So companies had to offer new sliced packaging format that could adapt with consumers' needs without affecting the organoleptic characteristics of the product. On the other hand, since we are dealing with a gourmet product of high sensory quality, results of this work would help companies in the sector to understand how the packaging format would influence the sensory attributes of the product. Both approaches applied in this article will allow industrials to know how consumer would behave in a pre and post‐purchase situation of different sliced dry‐cured Iberian ham packages that could be part of future marketing strategies within the Iberian sector.